PENGEMBANGAN TES LITERASI MEMBACA KRITIS-KREATIF UNTUK SISWA SMP - TITIK HARSIATI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The purpose of the study is to develop an instrument to assess critical-creative reading literacy. Research was conducted at Junior High School in Malang and Batu, East Java. Validity and reliability instrument were designedin three stages of calibrate: (1) panel of expert, (2) varied sample and population test, and (3) factor analysis. The population of the study was students of Junior High Schools. Samples were chosen based on stratified random sampling. Empirical test, using factor analysis and involving 307 students shows that dimension of the instrument developed theoretically agrees with the results of factor analysis. Result of research indicates that the critical-creative reading literacy test consists of four dimensions namely: (1) content comprehension, (2) critical comprehension, (3) creative comprehension, and (4) problem solving based on reading comprehension. The four dimensions were elaborated to make 14 factors. The result of factor analysis indicates that each factor has loading factor bigger than 0,30. Result of calibration of the critical-creative reading literacy test has coefficients reliability 0,798.